Study the relationship between the liver functions and interleukin- 10 in female thalassaemia patients in Kirkuk city - Afnan Y. Bakr; Mousa M. Marbut; Ahmed H.AL-Ani (Tikrit Journal of Pure Science)
This study was conducted in thalassaemia center at Azadi Teaching Hospital in Kirkuk city from the  beginning of August 2017 to the end of April 2018. One hundred female subjects were participated in the study (70)  thalassaemic patients and Thirty (30) persons as control group how they were non thalasaemic. with no family history of hereditary blood disease attendants to different clinics of Azadi hospital, who were assessed by a clinician. All subjects were aged between 8- 15 years. Age  and body mass index (BMI), were measured for all subjects in this study and used for the measurement of serum interleukin10, serum feritine, serum (GOT), Serum (GPT), serum (ALP) and total serum bilirubine.